Health and inequality : geographical perspectives - Curtis, Sarah (Online access: SAGE SAGE Research Methods Core., 2004)
By relating theoretical arguments to specific landscapes Sarah Curtis develops the basis for a geographical analysis of health problems and proposes a range of strategies for reducing disadvantage and societal inequalities.